DESULPHURIZATION OF NIGERIAN LAFIA COAL FOR METALLURGICAL COKE PREPARATION (1988)
The Government-owned integrated iron and steel plant under construction in Ajaokuta has been designed to operate through the blast-furnace process. The blast-furnace requires metallurgical coal. It therefore became necessary and relevant to the national economy to scientifically work on Nigerian coals with a view to using same as metallurgical coal. Lafia coal is the only Nigerian coal that produces coke lump after dry distillation (carbonization). The property of coke- ability therefore attracted attention towards Lafia coal. The main interest was to so prepare the coal that as much as possible of it will be usable for metallurgical coke preparation for use in Ajaokuta blast-furnace. Lafia coal was subjected to chemical characterization and petrological studies. It became clear that it was high in ash and sulphur. Silicates, pyrites and carbonates of various elements constituted the inorganic mineral inclusions. Analytical data gave the sulphur varieties in Lafia coal to be organic (0.1 - 0.7%), pyritic (1.4 - 4.4%) and sulphate (0.01 - 0.07%). Pyritic sulphur which predominates in Lafia coal can be removed by physical means. Chemical desulphurization which is reducto-oxidative type of chemical reaction impares coal cokeability. A plunge was thus made for physical desulphurization techniques to bring down the total sulphur in Lafia coal to the level that will make it acceptable as a metallurgical coal with regards to its sulphur content. Trace elements in Nigerian coal ash determined using the Atomic Absorption Spectrophotometer (AAS) and confirmed with the Inductively Coupled Plasma Emission Spectrophotometer (ICPES) showed that the relative abundance of the elements in the coals depended on the biogeo-chemistry of the area of the deposit as follows: Lafia coal; F>Zn>Mn»V Cr>Ni>Cu>B>Pb>Ca>Be>Mo>Cd>Hg Enugu coal; B>Mn>V F>Cr>Zn>Cu>Pb Ni>Co>Be>Mo>Hg Okaba coal; Mn»B»V>Cr>Cu>Pb>F=Ni>Zn Co>Be>Mo>Hg Trace element content of coal was considered in connection with the impact of coal utilization on the environment. From the study it was concluded that either the wet concentrating table or the froth flotation method could be used to substantially desulphurize Lafia coal to meet the requirement of metallurgical coal.